Vibration problems of an example of temporary steel grandstand under human-induced excitation = Problemy drgań przykładowej tymczasowej trybuny stalowej poddanej oddziaływaniom dynamicznym wywołanym przez ludzi - Lasowicz, Natalia; Jankowski, Robert (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
Lighter and slender structural members of a typical grandstand leads to a significant reduction in the frequencies, that is why such structures are more easily induced to vibrations. The aim of the present paper is to show the results of the experimental tests and the numerical analyses focused on the behaviour of a part of a typical temporary steel grandstand under dynamic loads.
Keywords: trybuny stalowe; obciążenia dynamiczne; wibracje wzbudzane przez ludzi; steel grandstands; dynamic loads; vibrations; human induced vibrations